Do when and where matter? Initial labor market conditions and immigrant earnings - Olof Åslund; Dan-Olof Rooth (Institute for Labour Market Policy Evaluation (IFAU), 2003)
This paper investigates the long-term effects on immigrant earnings and employment from labor market conditions encountered upon arrival. We find substantial effects both of the state of the national labor market and of local unemployment rates. Comparing refugees entering Sweden in a severe and unexpected recession to refugees arriving in a preceding economic boom, we attempt to handle the issue of selective migration. The analysis of effects at the local level exploits a governmental refugee settlement policy to get exogenous variation in local labor market conditions.
Keywords: F22; J15; J61; R23; 330; Immigration; earnings: labor market conditions